PLATELET AGGREGATION IN ACUTE CORONARY SYNDROME - Sulianty .; Adi K Aman (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Haemostatic system is the mechanism that controls response of bleeding or thrombosis, so that thrombogenesis and fibrinolysis are inbalance. Obstruction of brain and heart vascular system often occurred, because of the hyperactivity of thromboses function that causesthrombosis. CBC, blood glucose, lipid profile and cardiac enzyme assay were performed on acute coronary syndrome patients at theEmergency Department as well as at the normal control. In this study, each group consist of 10 patients. Platelet aggregation test wasmeasured with turbidimetric method using Helena Agram aggregometer. ADP and epinephrine 5 and 10 µM were used as the agonists.There was significant difference in the mean total cholesterol, LDL and blood sugar level in the acute coronary syndrome patients thanthe control group. Platelet aggregations with ADP 1 and 5 µM were significantly different in the acute coronary syndrome patients thanthe control one. In this study were found patients aged above 50 years old have platelet aggregation with ADP 10 µM, which differsignificantly than the control group.